2011
DOI: 10.1007/s10517-011-1131-4
|View full text |Cite
|
Sign up to set email alerts
|

Study of Anti-Ischemic Effect of Afobazole in Experimental Myocardial Infarction

Abstract: Seven-day treatment of rats with experimental myocardial infarction with afobazole (5-ethoxy-2-[2-morpholino)-ethylthio] benzimidasole dihydrochloride) resulted in shrinkage of the ischemic damage area in the heart, stimulation of reparative processes in the myocardium, and prevention of postinfarction remodeling of the left ventricle. Anti-ischemic effect of afobazole in experimental myocardial infarction is presumably due to its interactions with σ(1) receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Previous pharmacological studies have identified ligand interaction of afobazole with MT 1 (K i = 1.6E-05 M), MT 3 (K i = 9.7E-07 M), r1 (SigmaR1) (K i = 5.9E-06 M) receptors and MAO A (K i = 3.6E-06 M) and defined its main effects as anxiolytic and neuroprotective . Further studies revealed its cardioprotective action (Stoliaruk et al 2010;Kryzhanovskyi et al 2011) and protective action in various toxicological models (Durnev et al 2009). These findings confirmed previously postulated hypothesis of cytoprotective potential of this anxiolytic drug ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous pharmacological studies have identified ligand interaction of afobazole with MT 1 (K i = 1.6E-05 M), MT 3 (K i = 9.7E-07 M), r1 (SigmaR1) (K i = 5.9E-06 M) receptors and MAO A (K i = 3.6E-06 M) and defined its main effects as anxiolytic and neuroprotective . Further studies revealed its cardioprotective action (Stoliaruk et al 2010;Kryzhanovskyi et al 2011) and protective action in various toxicological models (Durnev et al 2009). These findings confirmed previously postulated hypothesis of cytoprotective potential of this anxiolytic drug ).…”
Section: Introductionmentioning
confidence: 99%